A STUDY ON THE IMPACT OF DAYTIME NAP ON DECLARATIVE MEMORY IN YOUNG ADULTS - A, CHRISTY; m, DIVYA; A, SARAVANAN; S, VADIVEL; K, Jaiganesh (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To evaluate the impact of the daytime nap on declarative memory assessed by performance of memory tasks in young adults. Methods: The study was carried out among 30 subjects, 15 males and 15 females divided into daytime napping group and control group. These subjects were allowed for 60 minutes retention interval. Later the subjects in daytime nap group were put to bed in a sound attenuated sleep chambers to enable napping while control group was kept awake. Performance of declarative memory was evaluated both pre and post intervention for all subjects by three tests namely, unrelated paired associates, maze learning, and the Rey–Osterrieth complex figure. Results: Statistical analysis revealed that independent t-value was significant between napping and awake group on memory task performance conducted before and after 60 minutes retention interval (p<0.001). Sleep parameters analysis in napping group show sleep onset latency time of 10.6 minutes, which was dominated by Stage I sleep with sleep efficiency of 56.35%. Total sleep time was 51.46 minutes in napping group. Improvement in memory task was statistically significant as the results of unrelated word pair's associates the performance of nap group was 97.2% when compared with the control group with 90% performance. Rey–Osterrieth complex figure test results show the average time taken by nap group was 45 seconds, and that of awake group was 63 seconds. In the case of maze learning task, the time taken by nap group was 27.33 seconds and by awake group was 38.2 seconds (p<0.001). Conclusion: From the results it is evident that non declarative memory is well enhanced by daytime napping shown by improved performance tests. This might be brought about by memory consolidation process triggered during sleep onset latency. Keywords: Daytime nap, Non-rapid eye movement sleep, Memory consolidation, Declarative memory task.